Effect of oral β-blocker treatment on mortality in contemporary post-myocardial infarction patients: a systematic review and meta-analysis. Issue 1 (6th September 2018) - Dahl Aarvik, Magnus; Sandven, Irene; Dondo, Tatendashe B; Gale, Chris P; Ruddox, Vidar; Munkhaugen, John; Atar, Dan; Otterstad, Jan Erik
Abstract: Aims: Guidelines concerning β-blocker treatment following acute myocardial infarction (AMI) are based on studies undertaken before the implementation of reperfusion and secondary prevention therapies. We aimed to estimate the effect of oral β-blockers on mortality in contemporary post-AMI patients with low prevalence of heart failure and/or reduced left ventricular ejection fraction. Methods and results: A random effects model was used to synthetize results of 16 observational studies published between 1 January 2000 and 30 October 2017. Publication bias was evaluated, and heterogeneity between studies examined by subgroup and random effects meta-regression analyses considering patient-related and study-level variables. The pooled estimate showed that β-blocker treatment [among 164 408 (86.8%) patients, with median follow-up time of 2.7 years] was associated with a 26% reduction in all-cause mortality [rate ratio (RR) 0.74, 95% confidence interval (CI) 0.64–0.85] with moderate heterogeneity ( I 2  = 67.4%). The patient-level variable mean age of the cohort explained 31.5% of between study heterogeneity. There was presence of publication bias, or small study effect, and when controlling for bias by the trim and fill simulation method, the effect disappeared (adjusted RR 0.90, 95% CI 0.77–1.04). Also, small study effect was demonstrated by a cumulative meta-analysis starting with the largest study showing no effect, with increasing effect as the smaller studies were accumulated. Conclusion: Evidence from this study suggests that there is no association between β-blockers and all-cause mortality. A possible beneficial effect in AMI survivors needs to be tested by large randomized clinical trials.